A Critical Analysis of Brentano’s Intentionality in Relation to Meinong’s Object Theory - Isenyo Solomon Ogaba (Borong Newinera Publisher, 2021)
Our thoughts are certainly about things(objects), however, what kind of things(object) are our thoughts directed at? What is the relationship between mental objects and external world object? What is the nature and character of mental and extra mental objects? An attempt at answering these meta-epistemological questions, brought to light the ideas of Franz Brentano on ‘Intentionality’ and Alexius Meinong’s Theory of object. Through proper method of philosophical analysis, it was discovered that both philosophers agreed that intentionality is a unique character exhibited by the human mind. However, Meinong went further to develop a more comprehensive object theory which attempts at clarifying some of the ontological difficulties associated with Brentano’s notion on intentionality. The research concluded that, though, both philosophers had areas of divergence and convergence in their respective epistemological thoughts, but insisted that the influence of Brentano’s ideas on Meinong cannot be overemphasized, which is to say, Meinong’s object theory, could be said to be a reaction towards the problem of referential opacity present in Brentano’s account of Intentionality.